Course of insight, depression and suicidality in inpatients with first‐episode schizophrenia who received group psychoeducation. Issue 9 (2nd November 2021) - Sato, Kojiro; So, Ryuhei; Yoshimura, Bunta; Kitagawa, Kohei
Abstract: Aim: We aimed to investigate whether gaining insight through psychoeducation for first‐episode schizophrenia is associated with increased suicidality. Methods: We conducted a secondary analysis of a prospective cohort study that included inpatients with first‐episode schizophrenia who attended a group psychoeducation program during their admission. The group psychoeducation program consisted of four weekly sessions provided by a multidisciplinary team. The primary outcome was the correlation between changes in insight and suicidality. We also examined whether change in insight was associated with changes in hopelessness and depression. We measured insight using the Birchwood Insight Scale. Suicidality, hopelessness and depression were measured using the Calgary Depression Rating Scale for Schizophrenia. Results: A total of 125 people participated in the educational program. The Spearman's correlation coefficient between changes in insight and suicidality was −0.14 (95% confidence interval, −0.31 to 0.04; p  = .12). Similarly, gain in insight did not significantly correlate with change in depression (0.01, 95% confidence interval, −0.17 to 0.18; p  = .93) and change in hopelessness (0.01, 95% confidence interval, −0.16 to 0.19; p  = .88). Conclusions: We observed almost no association between gaining insight and suicidality after a group psychoeducation program in inpatients with first‐episode schizophrenia.